Comment on Küppers et al. Percutaneous Anorectoplasty (PARP)-An Adaptable, Minimal-Invasive Technique for Anorectal Malformation Repair. Children 2022, 9, 587 - Alberto Peña (MDPI AG, 2022)
I read the above-mentioned article with a great deal of interest [...]